O presidente e a coordenação da sua agenda legislativa de políticas no Brasil - Rosiene Guerra de Andrade (2023)
The study examines the president's role in shaping their legislative agenda for public policies, aiming to comprehend how they manage this dynamic and employ the tools at their disposal to engage with their agents. Inherent risks within delegation relationships render no guarantee that agents will advance the objectives of their political principals. Therefore, instruments must be used to coordinate the construction of their agenda and mitigate such risks, as these can directly or indirectly affect government policies. Numerous studies have discussed factors influencing the use of these instruments, yet they often fail to highlight their consequences for public policies across various domains. This study seeks to bridge this gap by addressing two central questions: a) Which instruments does the president employ to intragovernmentally coordinate the formation of their legislative agenda for public policies across different areas and political contexts? b) What are the effects of the coordination instruments used by the president on their capacity to shape this agenda? The term "coordination instruments" denotes the actions of political principals in addressing challenges in order to minimize delegation issues and have their priorities recognized during the agenda-setting phase. Based on the Brazilian case, the aim is to assess whether the diverse instruments employed by presidents impact the outcome of coordination during the agenda-setting phase in multipartisan cabinets, considering the president's ability to draft legislative proposals, that is, whether or not the Executive presents legislative proposals in line with the President's priorities. To achieve this, the study introduces an indicator designating the presidential capacity for coordinating the formation of their legislative agenda. The overarching hypothesis underscores that under certain conditions, the more the president utilizes the available coordination instruments within their prerogative set, the higher the likelihood of aligning their policy agenda with their priorities. The study adopts a longitudinal research design (1990 to 2020) and qualitative and quantitative research approaches. In general, results revealed variations in the use of coordination instruments among presidents and demonstrated that the sole statistically significant evidence explaining agenda coordination is the overlap of ministerial competencies.